Potential of Bacillus subtilis as biological control agent for rice blast disease in MR219 rice cultivar - Soleimani, Narges (2014)
The present study focuses on the effect of Bacillus subtilis in rice blast disease reduction. This study was conducted in 3 experiments to investigate B. subtilis ability as a biological control agent in MR219 cultivar. Based on morphological characterization, Bacillus sp. were selected and purified on nutrient agar. Purified isolates were tested in vitro for antagonistic characteristics by dual culture assay. Out of all 54 bacterial isolates screened, 20 isolates showed some levels of antagonistic activity with two isolates having the strongest inhibitory activity of 57.40% and 62.96% based on percentage inhibition of radial growth (PIRG). Both strains were Gram-positive, rod shaped cells, motile, oxidase, catalase, urease, citrate and mannitol positive. PCR amplification using universal primers amplified a fragment of the expected size (900 bp) from the 16S rRNA gene. PCR products were purified and sequenced to identify the antagonistic strains. Strain B1 and B2 were identified with 98%similarity as B. subtilis strain QB928 (NC028520.1). Potential strains were subjected for culture filtrate test to detect the non-volatile diffusible inhibitors either as antibiotics, enzymes or other forms where culture filtrate of strain B1 and B2 were inoculated in nutrient broth and incubated for 7 days. The culture was centrifuged and filtered supernatant was incorporated into potato dextrose agar. The PIRG results suggested that administration of B1 and B2 strains can effectively inhibit mycelia growth by 75.43% and 64.79% respectively. Production of volatile compounds was determined using inverted culture plate method where mycelia growth of Pyriculraia oryzae was measured in incubated control, B1, and B2 treated petri dishes after 7 days. Results showed considerable reduction of antifungal activity for both strains of B1 and B2 which were 65.9% and 57.4% respectively, indicating volatile compound production in both strains culture. Glasshouse investigation showed the effect of both strains on MR219 rice variety where B. subtilis application significantly (α=0.05) reduced the severity of disease, with the highest reduction of 57% which was recorded in treatments receiving strain B1. The area under the curve for severity of blast disease was assessed and the results found to be significantly different (P< 0.05) where 368.9 square units was recorded for strain B2 and 299.1 square units for strain B1. Disease progress rate in rice plants treated with strain B2 was higher (0.15 unit/day) than in strain B1 (0.12 unit/day) meaning that disease development was more slowly in strain B1. In plants which have received antagonistic bacteria the reduced severity of disease resulted in a significantly higher rate of photosynthesis (32.01 μmolm-2s-1) compared to other plants. Shoot dry weight of rice plants increased significantly (0.18 g) with B. subtilis application. Although both strains were effective in decreasing the intensity of blast, greater effectiveness was achieved through B1 application. Accordingly, on the basis of the results of this study, both candidates might be very promising biological control agents for blast control on MR219 cultivar where blast resistant cultivars have become susceptible.